Constraining heterogeneity in the absorbed dose of 50 keV X-ray irradiated samples for EPR dating: simulation and experimental approaches - Bossin, L.; King, G. (Ancient TL, 2021)
X-band Electron Paramagnetic Resonance (EPR) of quartz requires the irradiation of samples with volumes of ca 3 mm3 , which can be conveniently achieved using commercially available instruments such as the 50 keV X-ray Dose manufactured by Freiberg Instruments. However, X-rays at such low energies can result in highly heterogeneous absorbed doses. In this contribution we use Monte-Carlo particle transport simulations (MCNP6) to characterise the heterogeneity of the radiation field in a 3 mm inner-diameter EPR sample tube irradiated using a 50 kV X-ray generator. From these simulations, we demonstrate that the use of an aluminium filter (200 µm) is redundant when irradiating samples in glass tubes (500 µm wall thickness). Simulations of grain-by-grain absorbed doses across the tubes indicate a maximum of 20 % axial heterogeneity for grains at the tube centre, even when the sample is rotated throughout irradiation. Single-grain luminescence dosimetry measurements were used to experimentally validate the heterogeneity predicted, confirming the modelling results. EPR dosimetry calibration of the X-ray source yielded a dose rate of 0.206 ± 0.005 Gy·s-1 .